Hypothesis of the scientific research - Rexhep Bujari Remzi; Ali Azemi Bashkim (Univerzitetska Misao, 2019)
To clarify the hypotheses of scientific research and their role, it is first necessary to clarify the hypothesis concept. The hypothesis is called the initial and unsafe assumption, but it is, however, unlikely to be verified, based on which the first explanations can be given about any occurrence, issue of relationships, problem, etc. They seek to find explanations, relationships, comparisons, predictions, generalizations, and theories. Assumptions should be formulated clearly and simply connected to your assumption for the expected results. It represents the starting point for defining goals and tasks. Any experimental or explanatory work starts waiting for a certain result. This expectation is the result of a hypothesis. Hypothesis initiative and provides incentives for research and affects the search method. Depending on the research hypothesis may be a theoretical or empirical puzzle. Research must have at least a hypothesis, which aims to provide answers. The researcher must determine which hypothesis is appropriate, develop new theories and concepts. The hypothesis should traditionally be "proved" as a statement or expression of the relationship between two or more concepts. "It is a proven assertion of the relationship or relationship between two or more concepts, reasonable interpretations of what we find in our analysis of texts, content, people or events. In the literature encountered different types of hypotheses, depending on the criteria to be taken to determine the type. We have the general hypothesis, auxiliary, null hypothesis, inductive, deductive, one-way, two-way, etc. All the hypotheses of a study must not only be based on reasoning or intuition, but in the first place should be formulated and tested on the database collected through observation of realworld phenomena as occur, or through experiments. Testing the hypothesis can be done in several ways, but testing through advanced software is more accurate and more reliable.